(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
This article investigates the relationship between the wool productivity of dromedary (single-humped) camels and their pasture areas in the conditions of the Ustyurt Plateau. It presents the observed variations in wool productivity and provides conclusions based on the findings.